Author Response: Prospective Natural History Study in 24 Adult Patients With LGMDR12 Over 2 Years of Follow-up: Quantitative MRI and Clinical Outcome Measures. (14th February 2023) - De Wel, Bram; Claeys, Kristl G.
Abstract : We read with interest the comments by Professor Kawada on our article. 1 As described in the article, all participants were evaluated 3 times within strict 1-year intervals; there were no missed visits or missing data. Furthermore, we defined disease onset as the start of clinical symptoms of limb-girdle muscular dystrophy autosomal recessive type 12 (LGMDR12) and thereby excluded patients with isolated hyperCKemia for increased phenotypic homogeneity.